Redesigning Educational Leadership Preparation for Equity : strategies for innovation and improvement - Young, Michelle D.; O'Doherty, Ann, 1959-; Cunningham, Kathleen M. W., 1982- (New York, NY : Routledge, 2022)
"Delivering equity for PK-12 learners is an essential aim for educational leadership preparation programs. This book serves as a resource for equity-focused design and redesign thorough innovation, improvement and impact. Based on direct experience while also drawing from innovative exemplars, and unpacking a decade of program improvement practice, this book explores how to foster partnerships and pipelines, recruit and select candidates, map the curriculum, develop powerful learning experiences, create field experiences, design program evaluation, and support faculty learning. Chapters open with a vignette that presents scenarios in which many faculty members find themselves, particularly when programs are in need of improvement. Drawing on years of experience facilitating redesign, the authors offer both processes and resources to assist faculty, including diagnostic tools, sample agendas, templates, guiding questions, and suggested protocols. Whether facing new accreditation requirements, state program approval changes, institutional redesign challenges or as part of a grant funded redesign, this book is a critical resource for educational leadership faculty and program coordinators looking to garner the appropriate resources, ask the right questions, and follow reliable processes in program design and continuous improvement toward equity"--
Getting ready for program design -- Fostering partnerships and leadership pathways -- Beginning with the end in mind -- Designing and Implementing a strategic plan -- Mapping the curriculum -- Fostering powerful learning experiences -- Delivering learning experiences -- Shaping field experiences -- Building supportive program structures -- Assessing candidate learning -- Recruiting and selecting -- Evaluating the program -- Supporting faculty learning, and organizational change.
Includes bibliographical references and index.
Keywords: School improvement programs -- United States; Educational equalization -- United States; Educational leadership -- United States